Design and implementation on orchestrator for heterogeneous SDN data center solutions - Linze WU; Yongbing FAN; Zhilan HUANG; Nan CHEN; Baohong LIN (Dianxin kexue)
The requirements of interoperability,unified management and orchestration for heterogeneous SDN data center solutions have been identified.Based on the study of heterogeneous SDN interoperability,northbound interface and orchestration technology,SDN Hub was proposed as the orchestrator to satisfy the requirements.The architecture and system design of SDN Hub was also presented.Experiment result proves SDN Hub achieves the design goal of multi-controller access and heterogeneous resource pool scheduling.